دور اﻟﺘﻐﺬﯾﺔ ﻓﻲ ﻣﺮﺣﻠﺔ اﻟﻄﻔﻮﻟﺔ اﻟﻤﺒﻜﺮة (3- 5 سنوات ( وبعض المتغيرات ودورها في اصابة الاطفال بتسوس الاسنان (Journal of the College of Education for Women, 2019)
Teeth decay is one of the distinctive diseases which infects the children of generation .though it is not adeacly disease, it leads to huge problems , especially if it is infect children in their early childhood .There are many factors which lead to this disease , and to achieve the goal of this research in trying to stop the most important nutrition factors and others reasons that have relation with this disease .The practical application has been done for four months on children , who have been chosen randomly of the age ( 3-5 years) of both sexes , infected with teeth decay , from Baghdad city ( al karkh and al rusafa ) , the number of children reached to 90 child , divided into tow groups 45 male , and( 45 )female .Again they have been divided three groups ( 3 years , 4 years , 5 years , each group with( 15) child of both sexes ) .Along with their parents or guardians , special interview or meeting also forms have been given to them which include some special information related to the research after finishing the practical application , and collecting the forms , and analyzing the results statistically the research has been reached to the following : 1- 50% of the children are non breastfed . 2- 45% of the children leave the baby bottle in their mouth especially at night , 3- 95% cavities in the upper jaws . 4- The factors which lead to the disease , have been divided into two groups : A-The external factors , which include : 1-The daily average of the eaten food , and the repetition of the daily nutrition , which is between –the eaten meal is little , which do not reach to the standar daily nutrition meals . also the quality is not good enough except for vitamin c. 2-Eating a lot of sugar and sweet up to 95% 3- There is a conncation between childs infection with teeth decay and the behavour of leaving the baby bottle in the mouth up to the average : a-Males of al karkh 0.85 b-female of al karkh0.74 c-malesof al rusafa 0. 71 d-femals of al rrusafa 0.9 4-cleaning the teeth before sleeping 40% B-internal factors as follows: 1-PH measuring of saliva , and the levels were : a-malesof al karkh reaches (5-6.3) b-females of al karkh reaches (5-7.4) c-males of al rusafa reaches (5.8-4.1) d-females of al rusafa (5.6-3.6) 2-using PH scale for identifying the acidic of the taken sweets , the level reach (5.3) 3-The teeth is covered with food remaining , and reaction with natural bacteria of the mouth .leaving this will lead to changing of the teeth color and their decay heredity factors is weake.The connection between it and the teeth decay is (0.2) According to the previous results , it is necessary to look for the methods of how to prevent the infection with teeth decay .Especially to the people about the role of health and nutrition education , and to emphasize o f the importance of the breastfeeding , and to prevent the child from buying sweets , and to returen to the natural resources , of food to ensure the rightful growth of psychally and mentally .